MODERNIZATION PROCESSES IN BUKHARA TEXTILE INDUSTRY IN THE YEARS OF INDEPENDENCE (Scientific journal of the Fergana State University, 2024)
This article describes the changes in the industrial sector of the Bukhara yarn-gas plant during the years of independence. A number of positive changes in the republic's light industry were also felt in the textile industry of Bukhara. There was a modernization process in the textile factory. Cooperation agreements in the fields of textile development were signed with a number of foreign countries. To the textile industry of Bukhara during the years of independence its history is discussed.